Playground usage and physical activity levels of children based on playground spatial features - Reimers, Anne Kerstin; Knapp, Guido (Journal of Public Health, 2017)
Aim Being outdoors is one of the strongest correlates of phys- ical activity in children. Playgrounds are spaces especially designed to enable and foster physical activity in children. This study aimed to analyze the relationship between the spa- tial features of public playgrounds and the usage and physical activity levels of children playing in them. Subjects and methods A quantitative, observational study was conducted of ten playgrounds in one district of a middle-sized town in Germany. Playground spatial features were captured using an audit instrument and the playground manual of the town. Playground usage and physical activity levels of chil- dren were assessed using a modified version of the System for Observing Play and Leisure Activity in Youth. Negative bino- mial models were used to analyze the count data. Results The number of children using the playgrounds and the number of children actively playing in them were higher in those with more varied facilities and without naturalness. Girls played more actively in playgrounds without multi-purpose areas. Cleanliness, esthetics, play facility quality, division of functional areas and playground size were not related to any outcome variable. Conclusion Playground spatial features are related to play- ground usage and activity levels of the children in the play- grounds. Playgrounds should offer a wide variety of play fa- cilities and provide spaces for diverse play activities to re- spond to the needs of large numbers of different children and to provide activity-friendly areas enabling their healthy development.
Keywords: Physical activity; Playgrounds; Play facilities; Children; Audit instrument; Direct observation